Nanosponges: A Novel Drug Delivery System - Pawar, Dr. Ashish Y. (Asian Journal of Pharmaceutics (AJP), 2016)
The invention of nanosponges (NSs) has become a significant step toward overcoming the problems associated with conventional drug delivery. NS drug delivery system has emerged as one of the most promising fields in life science. These small sponges circulate around the body until they encounter the target site and stick on the surface and began to release the drug in a controlled and predictable manner which is more effective for a particular given dosage. The development of new colloidal carrier called NSs has the potential to solve these problems. Both lipophilic and hydrophilic drugs can be loaded in NSs. NS is a novel and emerging technology which offers controlled drug delivery for topical use. They can be crafted for targeting drugs to a specific site, prevent drug and protein degradation, and prolong the drug release in a controlled manner. NSs play a key role in targeting drug delivery in a controlled manner. In this review article, application of NSs, its preparation methods, and evaluation have been discussed.